263. EFFECTS OF PREHABILITATION AND POST-OPERATIVE HIGH-FLOW NASAL CANNULA AFTER OPEN ESOPHAGECTOMY ON PULMONARY COMPLICATIONS: A FEASIBILITY STUDY. (24th September 2022) - Vecchiato, Massimo; Deana, Cristian; Ziccarelli, Antonio; Raimondi, Paola; Martino, Antonio; Pontoni, Marta; Patruno, Vincenzo; Bassi, Flavio; Petri, Roberto
Abstract: Pulmonary complications (PPC) are still reported in 30% of patients also after minimally-invasive esophagectomy in high volume centers. 1–2. Prehabilitation programs are promising in ERAS protocols. 3 Open esophagectomy (OE) has the lowest anastomotic leakage rate but higher PPC.4, 5. The combination of pre-habilitation and the application of High-Flow Nasal Cannula (HFNC) after OE has not been investigated yet. This is a feasibility study evaluating a pre-habilitation program and the post-operative application of HFNC on PPC after OE. We prospectively included patients undergoing OE from May 2021 to February 2022. A preoperative multimodal prehabilitation program was applied to all patients. Within 4 hours after surgery, patients were extubated and put under HFNC (50–60 lt/min with FIO2 0.4, humidifier temperature at 34°C) for the following 5 days. Chest physiotherapist applied daily post-operative respiratory exercise to all patients. Hospital stay outcomes, feasibility of HFNC and PPC were recorded by 30 days after surgery. We compared this group with an historic cohort (January 2016–March 2021) where HFNC was not applied to determine differences in baseline characteristics and post-operative complications. We included 45 patients for the final analysis, 12 in the HFNC and 33 in the historic cohort. Baseline characteristics comparisons are shown in table 1 . No interruption of post-operative HFNC was recorded due to patient's complain. PPC in the two groups were statistically comparable. No adverse event was related to HFNC application. The overall leakage rate was 9%. A prehabilitation program and HFNC use after OE seems feasible, safe and well tolerated by patients. PPC were lower in the treatment group without statistically significant difference. Pneumonia was recorded in less than 20% of patients; in the study group there weren't severe pulmonary complications (ARDS, reintubations). HFNC looks like an interesting tool for post-operative respiratory support. Larger randomized controlled trials should be designed to evaluate HFNC efficacy after esophagectomy.